Pemilu Serentak 2029 Pasca Putusan MK: Antara Kepastian Konstitusi Dan Kekacauan Regulasi - Saeful Rohman, Prista Kelana (ARBITER: Jurnal Ilmiah Magister Hukum, 2026)
This article aims to analyze the upcoming 2029 simultaneous elections following the Constitutional Court's ruling No. 135/PUU-XXII/2024. The focus is on regulations and the quality of democracy in Indonesia. To approach this issue, theoretical references from constitutional democracy and the theory of the electoral system in Indonesia from 2004 to 2024 are used. Data were collected through a literature review with primary sources being the Constitutional Court's ruling No. 135/PUU-XXII/2024, Law No. 7 of 2017 concerning Elections, and the General Elections Commission (KPU) technical documents and regulations, along with relevant academic literature. All data were analyzed qualitatively using a normative approach to uncover the gap between constitutional norms and their implementing regulations. This study concludes that the Constitutional Court's ruling No. 135/PUU-XXI/2024 was intended to affirm constitutional certainty, but this decision has instead created regulatory chaos because it has not been followed by comprehensive legal reforms. This regulatory vacuum and inconsistency have the potential to undermine election integrity, increase political costs, and threaten the quality of inclusive and accountable democracy in Indonesia ahead of the 2029 elections. As an alternative, a clear transitional design is needed, including scheduling regional elections a maximum of 2.5 years after the national elections, as mandated by the Constitutional Court's ruling. The formulation of transitional norms is needed as a mitigating measure against the potential regulatory vacuum, while also ensuring the order of the legal system during the transition period following the Constitutional Court's ruling. This scheme is expected to maintain the consistency of the principle of simultaneity functionally, provide legal certainty for organizers, and enable synchronization of budget planning and election stages without disrupting the stability of the central and regional governments.